2017
DOI: 10.1111/jcmm.13153
|View full text |Cite
|
Sign up to set email alerts
|

EZH2‐mediated repression of Dkk1 promotes hepatic stellate cell activation and hepatic fibrosis

Abstract: EZH2, a histone H3 lysine‐27‐specific methyltransferase, is involved in diverse physiological and pathological processes including cell proliferation and differentiation. However, the role of EZH2 in liver fibrosis is largely unknown. In this study, it was identified that EZH2 promoted Wnt pathway‐stimulated fibroblasts in vitro and in vivo by repressing Dkk‐1, which is a Wnt pathway antagonist. The expression of EZH2 was increased in CCl4‐induced rat liver and primary HSCs as well as TGF‐β1‐treated HSC‐T6, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 29 publications
(35 reference statements)
1
33
0
Order By: Relevance
“…In conclusion, it is important to note that epigenetic regulators, including EZH2, have described roles in other liver cell types beyond cholangiocytes . In fact, our group and others have previously shown a pro‐fibrotic role for EZH2 in HSCs .…”
Section: Discussionmentioning
confidence: 62%
“…In conclusion, it is important to note that epigenetic regulators, including EZH2, have described roles in other liver cell types beyond cholangiocytes . In fact, our group and others have previously shown a pro‐fibrotic role for EZH2 in HSCs .…”
Section: Discussionmentioning
confidence: 62%
“…They showed that EZH2 may contribute to peroxisome proliferator-activated receptor γ transcriptional silencing in a relay pathway along with methyl CpG binding protein 2 and microRNA132. It also has been reported that EZH2-mediated repression of Dkk-1 may promote activation of the Wnt/β-catenin pathway, 29 which has been shown to contribute to HSC transdifferentiation. 30 Our results consistently confirm the profibrotic role of EZH2 in vitro and in vivo, corroborating its potential as a target for antifibrotic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The profibrogenic role of the Wnt/β‐catenin signaling pathway in endometriosis has recently been reported . EZH2 can also suppress Dkk1, a negative regulator of the Wnt/β‐catenin signaling, inducing fibrosis . Again, Dkk1 expression is reported to be reduced in endometriosis …”
Section: Mutations Of Cancer Driver Genes In Endometriosis and Their mentioning
confidence: 97%